What factors are associated with unplanned return following transurethral resection of bladder tumor? An analysis of a large single institution's experience. (2nd September 2016) - Ghali, Fady; Moses, Rachel A.; Raffin, Eric; Hyams, Elias S.
Abstract: Objective: This study sought to evaluate factors associated with unplanned hospital return (UR) following transurethral resection of bladder tumor (TURBT), the largest source of readmission among ambulatory urological procedures. Materials and methods: A retrospective review of TURBTs at a single academic institution between April 2011 and August 2014 was performed. Demographics, comorbidities, length of stay, tumor size and multiple other factors were recorded. UR was recorded within 30 days of surgery. Bivariate and multivariable analyses were performed to determine factors associated with UR. Results: Among 708 patients undergoing TURBT, 23.9% were female with a mean age of 70 years. The rate of UR was 10.9%. The most common cause of UR was gross hematuria, accounting for 70%. On bivariate analysis, Foley catheter placement in the operating room, non-aspirin anticoagulation and index length of stay longer than 24 h were associated with hematuria-related UR ( p < 0.05). Preoperative antibiotics, female gender and aspirin therapy were associated with lower rates of hematuria-related UR ( p < 0.05), while tumor size, distance of residence to the hospital, and Foley on hospital discharge (rather than from the operating room) had no association ( p > 0.05). On multivariable analysis, only Foley placement in the operating room remained associated with higher rates of hematuria-related UR, while preoperative antibiotics, female gender and aspirin therapy remained associated with a lower likelihood of this event. Conclusions: UR following TURBT is common and typically results from gross hematuria. Patients with postoperative Foley catheterization in the operating room may require additional counseling or supervision before discharge, and should be considered for discharge with a Foley rather than having a prompt voiding trial.